2005
DOI: 10.1128/jvi.79.21.13250-13261.2005
|View full text |Cite
|
Sign up to set email alerts
|

Complex Determinants in Human Immunodeficiency Virus Type 1 Envelope gp120 Mediate CXCR4-Dependent Infection of Macrophages

Abstract: Host cell range, or tropism, combined with coreceptor usage defines viral phenotypes as macrophage tropic using CCR5 (M-R5), T-cell-line tropic using CXCR4 (T-X4), or dually lymphocyte and macrophage tropic using CXCR4 alone or in combination with CCR5 (D-X4 or D-R5X4). Although envelope gp120 V3 is necessary and sufficient for M-R5 and T-X4 phenotypes, the clarity of V3 as a dominant phenotypic determinant diminishes in the case of dualtropic viruses. We evaluated D-X4 phenotype, pathogenesis, and emergence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 71 publications
3
48
0
Order By: Relevance
“…The results of our mutagenesis studies confirmed that Ile326 is critically important for efficient HIV-1 entry into macrophages by both SG3 and Macs1-Spln Envs. Our results support and extend the findings of Ghaffari et al (28), where, in a reciprocally designed experiment, replacement of Met for Ile at position 326 in two non-M-tropic CXCR4-using Envs enhanced macrophage entry via CXCR4. Together, these studies provide independent evidence that affirms a critical role for Ile326 in promoting efficient CXCR4-mediated HIV-1 entry into macrophages.…”
Section: Fig 4 Env Sequence Alterations Associated With Efficient Csupporting
confidence: 82%
See 1 more Smart Citation
“…The results of our mutagenesis studies confirmed that Ile326 is critically important for efficient HIV-1 entry into macrophages by both SG3 and Macs1-Spln Envs. Our results support and extend the findings of Ghaffari et al (28), where, in a reciprocally designed experiment, replacement of Met for Ile at position 326 in two non-M-tropic CXCR4-using Envs enhanced macrophage entry via CXCR4. Together, these studies provide independent evidence that affirms a critical role for Ile326 in promoting efficient CXCR4-mediated HIV-1 entry into macrophages.…”
Section: Fig 4 Env Sequence Alterations Associated With Efficient Csupporting
confidence: 82%
“…In addition, little is known about gp120-coreceptor interactions that may contribute to efficient CXCR4-mediated HIV-1 entry into macrophages. Although one previous study identified Ile326 in the gp120 V3 loop as being important for CXCR4-mediated HIV-1 entry into macrophages (28), the mechanism by which this amino acid variant permits macrophage entry is unknown. Here, we identified and characterized alternative mechanisms of coreceptor engagement by HIV-1 Envs that have efficient CCR5-and CXCR4-mediated entry into macrophages.…”
mentioning
confidence: 99%
“…2A). Consistent with previous studies, ADA and 89.6 Envs entered PBMC and MDM, whereas HXB2 Env entered PBMC but not MDM (18,19,34,42,43,(49)(50)(51). All C2 and DR Envs entered PBMC, but only C2-16 and DR-17 Envs entered MDM.…”
Section: Vol 80 2006supporting
confidence: 77%
“…While many HIV-1 strains can use either CCR5 or CXCR4 (R5X4 viruses) to infect cell lines, the efficiency with which a given virus uses each coreceptor for infection can vary widely and does not always predict the mechanism of entry into human T cells or macrophages (18). Thus, some R5X4 viruses use only CXCR4 to infect certain primary cells, others use only CCR5, and some viruses use both coreceptors to infect multiple cell types (16,17,26,36,(59)(60)(61). The use of specific and potent coreceptor antagonists can be utilized to prevent entry via one coreceptor, revealing the efficiency with which the alternative coreceptor can support virus infection.…”
mentioning
confidence: 99%